On mass forces in deformation zones at rolling in modern and small-section wire mills - V. V. Fillippov; V. A. Tischenko; A. D. Shevchenko; A. A. Gorbanev; S. M. Zhuchkov (Литьë и металлургия)
Steel reinforcement — tendencies and perspectives.